Metal ion sensing multi-functional differently octasubstituted ionophore chiral metallophthalocyanines: Synthesis, characterization, spectroscopy, and electrochemistry - ÖZKAYA, ALİ RIZA; KOCA, ATIF (ELSEVIER SCI LTD, 2007)
Multi-functional, differently octasubstituted ionophore chiral metallophthalocyanines (MPc's where M = Ni, Cu, Co and Zn), bearing reactive functionalities on the periphery, propane 1,2-diolsulfanyl moieties, which facilitated solubility in polar solvents and metal ion binding, were prepared from the corresponding anhydrous metal salts and differently substituted 4-(1,2-propanediolsulfanyl)-5-chlorobenzene-1,2-dicarbonitrile compound. The reactivity of the peripheral groups of the synthesized We's towards several metal ions was determined spectrophotometrically resulting in the formation of polynuclear phthalocyanine complexes. In all ionophore phthalocyanines, peripheral 1,2-propanediolsulfanyl moieties serve as exocyclic binding sites for a number of metal ions for further reactions after phthalocyanine formation, and also provide solubility of the phthalocyanines in protic solvents. The newly synthesized ligand and MPc's were characterized by elemental analysis, FTIR, H-1 NMR, C-13 NMR, MS (El and FAB), UV/Vis and Atomic Absorption Spectroscopy. The electrochemical behaviours of the complexes have also been investigated. Electrochemical studies reveal that cobalt phthalocyanine indicated two metal-based and three ligand-based redox processes while nickel phthalocyanine and copper phthalocyanine showed three ligand-based reduction and one ligand-based oxidation processes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanines; phthalonitrile; chiral; sensor; ionophore; electrochemistry; PHTHALOCYANINATO VANADYL; COMPLEXES; PORPHYRAZINES; MONOAZACROWN; DERIVATIVES; PALLADIUM; NITRO